An appropriate international monetary order for developing countries? - Gabriele Ullrich (Intereconomics, 1981)
The mounting balance of payments difficulties of most developing countries raise the question whether they are not aggravated by an international monetary system which is tailored to the requirements of industrialized countries and how the existing system could possibly be adapted to the needs of the developing countries. Dr. Ullrich is examining this question, using Black Africa as an example. The countries there are very similar in their historical and economic development and are all integrated in the western monetary system.
Keywords: 330; Monetary Policy